CORRELATION BETWEEN THE RISK OF FALL WITH INCIDENT OF HYPERTENSION IN THE ELDERY - Meitha Tibyana; Mustriwi Mustriwi (Program Studi Keperawatan, Fakultas Ilmu Kesehatan, ITSK RS dr Soepraoen, 2024)
The health of the elderly has a significant impact on a number of diseases. Hypertension is one of the illnesses that is frequently observed in the elderly. Blood flow to the heart muscles will become restricted if the heart's blood arteries are damaged. This may contribute to heart attacks, which raises the risk of falls in older people with a history of high blood pressure. The aim of this study are correlation between the risk of fall with incident of hypertension in the eldery. The design of this study used cross- sectional study. The population of study are elderly with hypertension in Lumbangsari Village, Bululawang District, Malang Regency, Indonesia. The sample of this study 58 respondent and used total sampling. Instrument of this variable used questionnaire. An overview of the degree of fall risk in older adults with hypertension is the variable under study. Analysis of this study used spearmank rank. The result of this study show that of the level of risk of fall in elderly hypertensi. Eldery who have high risk of fall (48.3%), moderate risk of fall (27.6%) and small risk of fall (24.1%). Level of hypertension are hypertension grade 2nd (48%), hypertension grade 1st (34%) and prehypertension (18%). There is positive correlation between level of risk and incident of hypertension with R=0.67 and p- value= 0.02. These results are influenced by several factors, namely age, gender, education, occupation, income, disease, smoking, excessive salt consumption. Based on this research, it can motivate elderly, to better maintain their diet and always maintain safety and health. Risk of fall eldery with hypertension can be decreased with preventive measures that can be given to the eldery.